Chemokine-Like Factor 1 (CKLF-1) is Overexpressed in Keloid Patients: A Potential Indicating Factor for Keloid-Predisposed Individuals. Issue 11 (March 2016) - Zhang, Mingzi; Xu, Ying; Liu, Yifang; Cheng, Yingying; Zhao, Pengxiang; Liu, Hao; Wang, Youbin; Ma, Xuemei
Abstract : Abstract: Chemokine-like factor 1 (CKLF-1) is a novel cytokine which have a crucial role in immune and inflammatory responses. In this study, the expression level of CKLF-1 was measured to assess the difference between keloid patients and people without keloid. Fifty samples were taken from 30 patients: 10 keloid patients; 10 scar patients; and 10 patients without obvious scarring. Patients were randomly selected from the hospitalized patients of Peking Union Medical College Hospital from September 2013 to July 2015. Five groups of samples were established: keloid samples from keloid patients (K); normal skin samples from keloid patients (KS); scar samples from scar patients (C); normal skin samples from scar patients (CS); and normal skin samples from patients without obvious scarring (S). Hematoxylin and eosin (H&E) staining was used to observe morphological changes. CKLF-1, IL-6, IL-8, IL-18, and TGF-β were detected by immunohistochemical and western blot technology. The expression of CKLF-1's mRNA was also measured by the real-time quantitative polymerase chain reaction (RT-qPCR). Compared to the K group, the other 4 groups presented significantly less inflammatory infiltration and lower expression levels of CKLF-1, IL-6, IL-8, IL-18, and TGF-β. Among the 3 normal skin groups, the expression level of CKLF-1 was significantly higher in the KS group than in the CS or S group. The mRNA expression was also obvious in the K and KS groups. CKLF-1 and other inflammatory factors were overexpressed in the samples from keloid patients, indicating that the formation of keloid may be related to inflammation and that CKLF-1 may play an important role in this process.